N6-methyladenosine methyltransferase KIAA1429 elevates colorectal cancer aerobic glycolysis via HK2-dependent manner. Issue 5 (2nd May 2022) - Li, Ying; He, Liang; Wang, Yingkai; Tan, Yan; Zhang, Fan
ABSTRACT: Emerging evidence has emphasized the critical roles played by N 6 -methyladenosine RNA (m 6 A) modification in colorectal carcinoma (CRC) initiation and progression. However, the roles and mechanism of m 6 A and KIAA1429 in CRC progression require further clarification. Here, our research aimed to investigate the functions of KIAA1429 in CRC tumorigenesis. Results indicated that KIAA1429 up-regulation closely correlated to the poor prognosis of CRC patients. Bio-functional assays demonstrated that KIAA1429 promoted the aerobic glycolysis, including glucose uptake, lactate production, ATP generation and extracellular acidification rate (ECAR). Mechanistically, KIAA1429 positively up-regulated HK2 level via increasing its mRNA stability by binding the m 6 A site of HK2 mRNA via m 6 A-independent manner. Collectively, our work indicates that KIAA1429 has the potential to promote CRC carcinogenesis by targeting HK2 via m 6 A-independent manner, providing insight into the critical roles of m 6 A in CRC. Graphical abstract: uf0001